HARMONIZING UNIVERSITY ENGLISH INSTRUCTION WITH STUDENT PREFERENCES: A QUALITATIVE STUDY OF PEDAGOGICAL ALIGNMENT IN EFL CONTEXTS - Novy Yuliyanti; Romadhon Romadhon (ELP (Journal of English Language Pedagogy), 2026)
Despite the global importance of English, many university students still struggle to achieve expected English proficiency. This study explores the gap between lecturer teaching methods and student learning preferences in English courses at a university in Cilegon, Indonesia. Using a qualitative approach based on Communicative Language Teaching (CLT) and Affective Filter Theory, semi-structured interviews were conducted with 15 students and 5 lecturers. The data were analyzed using thematic analysis by Braun and Clarke. The findings show a clear mismatch between teaching methods and student preferences. While 80% of lecturers used theory-focused teaching, 87% of students preferred practical and communicative activities. Differences were also found in the use of technology, where lecturers mainly used digital tools for delivering materials, while students preferred learning through songs and films. These differences increased students’ anxiety about making grammar mistakes. The study shows that learning difficulties are influenced more by teaching approaches than by students’ motivation to learn.